2014
DOI: 10.1364/oe.22.019912
|View full text |Cite
|
Sign up to set email alerts
|

High pulse energy multiwatt Yb:CaAlGdO_4 and Yb:CaF_2 regenerative amplifiers

Abstract: We investigated and compared Yb:CaAlGdO4 and Yb:CaF2 regenerative amplifiers at repetition rates 5-10 kHz, a frequency range interesting for industrial applications requiring relatively high pulse energy. Both materials allow for pulse energies close to 1 mJ with sub-400-fs pulses. The two laser materials offer comparable performance in the pump power range investigated. The same regenerative amplifiers can be run up to 500 kHz for much faster material processing, with maximum output power of up to 9.4 W.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…However, so far there is not one kind of electro-optic crystal or configuration the can provide a general solution under different operating wavelengths, repetition rates, spot diameters, and output powers. At present, BBO crystal Pockels cells with minimal piezoelectric ringing and low acoustic noise, have emerged in high repetition rate (>100 kHz) pulse picking applications [14][15][16][17]19]. Nevertheless, with the increase of repetition rate, it is difficult to realize fast switching within the effective duty cycle due to the long fall time of the high voltage.…”
Section: Experimental Principle and Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…However, so far there is not one kind of electro-optic crystal or configuration the can provide a general solution under different operating wavelengths, repetition rates, spot diameters, and output powers. At present, BBO crystal Pockels cells with minimal piezoelectric ringing and low acoustic noise, have emerged in high repetition rate (>100 kHz) pulse picking applications [14][15][16][17]19]. Nevertheless, with the increase of repetition rate, it is difficult to realize fast switching within the effective duty cycle due to the long fall time of the high voltage.…”
Section: Experimental Principle and Setupmentioning
confidence: 99%
“…Determined by the parameters of Pockels cell and regenerative cavity, repetition rates from hundreds to mega-Hz have been obtained with output power up to 100 watts. For instance, Nd:YVO 4 picosecond regenerative amplifiers with a repetition rate up to 850 kHz have been demonstrated [14,15]; other broadband gain materials such as Yb:CaF 2 , Yb:CAlGO, Yb:YVO 4 , and Nd:LuVO 4 show up to 1.43 MHz repetition rate [16][17][18]. Currently, Bergmann et al [19] reported the record high repetition rate of 2 MHz for a picosecond regenerative amplifier in Yb:YAG.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that, when seeded by optimized broadband sources, Yb:YAG systems have the capacity to support 0.5-2 ps pulse widths at 100 W to kW average power levels [6][7][8][9]. Unfortunately, in terms of pulse width, this performance is at the edge for several applications [10] and the search for alternative thermo-mechanically strong host materials with broader bandwidth has been ongoing [11][12][13][14]. It is clear that other approaches such as nonlinear spectral broadening for pulse shortening could also benefit from shorter seed pulses [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although not so aggressive in heat removal, laser systems based on bulk materials generally employ simpler structures and work more efficiently. These characteristics make bulk materials favored choices as laser media in high-power diode-pumped solid state lasers [12][13][14] . An average output power of 34 W with pulses as short as 140 fs at a 500 kHz repetition rate has been achieved by a bulk Yb:CALGO regenerative amplifier with the implementation of the chirped pulse amplification (CPA) technique [15] .…”
Section: Introductionmentioning
confidence: 99%